The Effect of Chemistry Learning with PjBL and PBL Model Based on Tetrahedral Chemistry Representation in term of Student’s Creativity - Frenika Widyasari; Nurma Yunita Indriyanti; Sri Mulyani (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2018)
This research aims to know: (1) the effect of PjBL and PBL models based on tetrahedral chemistry representation toward student’s achievement; (2) the effect of creativity toward student’s achievement; and (3) the interaction between PjBL and PBL models based on tetrahedral chemistry representation with creativity toward student’s achievement on the colloid subject in SMA Negeri 1 Sragen. This research used quasi experiment method with 2×2 factorial design. Samples of research were determined with cluster random sampling technique and used 2 classes in SMA Negeri 1 Sragen. Data has been collected by test, questionnaire, observation, and literature documents which owned by teacher. Hypothesis testing of this research for cognitive and skill aspects of learning achievement used parametric test of Anova two ways, and for attitude aspect of learning achievement used non-parametric test of Kruskal-Wallis. The results of this research showed that: (1) there was no effect of chemistry learning using of PjBL and PBL models based on tetrahedral chemistry representation toward knowledge, attitude, and skill aspects of student’s achievement; (2) there was effect of high and low creativity toward knowledge and skill aspects of student’s achievement but there was no effect toward attitude aspect of student’s achievement; and (3) there was no interaction between using PjBL and PBL models based on tetrahedral chemistry representation with creativity toward knowledge, attitude, and skill aspects of student’s achievement.